IMPLEMENTASI PENANGANAN KLIEN REHABILITASI NARKOTIKA JALUR COMPULSORY DAN VOLUNTARY DI BADAN NARKOTIKA NASIONAL KOTA JAKARTA SELATAN - Afrah Dizar Hafizhah; Retna Hanani (Journal of Management and Public Policy, 2026)
Narcotics abuse in Indonesia remains a serious issue that requires comprehensive handling, one of which is through rehabilitation policies as regulated in Law Number 35 of 2009 concerning Narcotics. This study aims to analyze the implementation of Article 54 and Article 103 of Law Number 35 of 2009 in the management of narcotics rehabilitation clients through compulsory and voluntary paths at the National Narcotics Board (BNNK) of South Jakarta, as well as to identify the supporting and inhibiting factors in its implementation. This research employs a qualitative method with a descriptive approach. Data collection techniques were conducted through in-depth interviews and observations with informants consisting of the Head of the Rehabilitation Section, rehabilitation counselors, the Head of the Rehabilitation Clinic, and rehabilitation clients at BNNK South Jakarta. The research analysis utilizes George C. Edward III's policy implementation theory, which includes communication, resources, disposition, and bureaucratic structure. The results indicate that the implementation of narcotics rehabilitation at BNNK South Jakarta has been carried out in accordance with the provisions of Law Number 35 of 2009 through both compulsory and voluntary paths. However, its implementation has not been fully optimal. The main obstacles include limited human resources and low levels of recovery motivation among compulsory path clients. Meanwhile, the supporting factors for the implementation of rehabilitation include the existence of clear regulations, the high commitment of rehabilitation officers in providing services, and well-established inter-institutional coordination.